2019
DOI: 10.1002/jcb.28567
|View full text |Cite
|
Sign up to set email alerts
|

Expression of γ‐H2AX and patient prognosis in breast cancer cohort

Abstract: H2AX phosphorylation is a novel marker of DNA double-stranded breaks. In the present study, we assessed the γ-H2AX expression, its association with other clinicopathologic characteristics, and the prognosis in a cohort of 97 patients with breast cancer. Ninety-seven specimens of tumor tissue and 77 adjacent normal tissues from patients with breast cancer were examined. All patients underwent modified radical mastectomy or local tumor resection without lymph node dissection. γ-H2AX expression was assessed by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…ɣH2A.X serve as an signal that aids in the recruitment of DNA repairing machinery to the site of breakage [109]. Higher ɣH2A.X level has been reported in breast cancer patient samples and in triple negative breast cancer cells as well [110,111]. ɣH2A.X is also been reported to function via TRAF6-ATM-H2AX signaling axis mediated by Hypoxia inducible factor 1α (HIF1α) [108].…”
Section: Macroh2amentioning
confidence: 99%
“…ɣH2A.X serve as an signal that aids in the recruitment of DNA repairing machinery to the site of breakage [109]. Higher ɣH2A.X level has been reported in breast cancer patient samples and in triple negative breast cancer cells as well [110,111]. ɣH2A.X is also been reported to function via TRAF6-ATM-H2AX signaling axis mediated by Hypoxia inducible factor 1α (HIF1α) [108].…”
Section: Macroh2amentioning
confidence: 99%
“…Therefore, immunostaining for γ-H2AX may be a useful tool to predict the genotoxicity and carcinogenicity of chemical substances 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 . The potential clinical applications of γ-H2AX immunostaining, such as prediction of cancer progression and response to radiotherapy, are also being investigated 20 , 21 . In bladder cancer, there may be a correlation between γ-H2AX formation in cancer cells and the risk of recurrence 22 , 23 , and γ-H2AX levels in peripheral leukocytes can be used as predictive factors for high-risk patients 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the phosphorylated histone H2AX (γ-H2AX) marker has become a robust tool used to monitor DNA DSBs in cancer research and has been suggested to play a potential role in carcinogenesis and early cancer diagnosis. 12 Accordingly, studies have revealed a correlation between high γ-H2AX levels and worse prognosis and reduced disease-free survival in breast cancer, 28 ovarian cancer, 29 and hepatocellular carcinoma. 30 Interestingly, an association of H2AXpositive OSCC with reduced overall survival has been reported.…”
Section: Discussionmentioning
confidence: 99%